Comparing the effects of ultraviolet radiation on four different encapsulants for photovoltaic applications in the Atacama Desert. (1st November 2021) - Correa-Puerta, Jonathan; Ferrada, Pablo; Häberle, Patricio; Díaz-Almeida, Daniel; Sanz, Asier; Zubillaga, Oihana; Marzo, Aitor; Portillo, Carlos; del Campo, Valeria
Highlights: Ultraviolet degradation of encapsulants for photovoltaic modules. Accelerated indoor UV-aging for photovoltaics devices. Transmittance of UV degraded polymeric encapsulants. Indoor UV irradiation of encapsulants related to the Atacama Desert UV conditions. Raman Spectroscopy for analyzing the degradation of encapsulants in c-Si based PV modules. Abstract: The performance of photovoltaic modules is highly dependent on the properties of the materials used to build them and is particularly sensitive to the type of encapsulant in the case of harsh outdoor environments. In this study, we compared the effects of ultraviolet (UV) radiation, under laboratory accelerated aging conditions, of four encapsulants: thermoplastic olefin, thermoplastic polyurethane, silicone, and ethylene vinyl acetate. The operation of the indoor ultraviolet chamber, using a mercury/xenon arc lamp as a radiation source, was related to the Atacama Desert ultraviolet conditions to estimate the corresponding time under outdoor conditions. The total indoor experiment time corresponded to 24.7 years of UV-B and 1.34 years UV-A irradiation. Transmittance in the ultraviolet–visible range, together with Raman spectra were analyzed to assess the effect of ultraviolet degradation. The aged encapsulants showed a transmittance reduction between 2% and 5% and a displacement in the ultraviolet cut off to higher wavelengths of around 5 nm. This information was used to compute the potential effect on the photogenerated current density of crystalline silicon photovoltaic modules, which decreased between 1% and 4%. Raman spectroscopy indicated the degradation of the encapsulants' polymer structure as an increment in the fluorescence of the spectra, above 50%, and modifications in the relative intensities of the encapsulant́s active Raman modes.